Evaluation of the changes of SpCO index in patients with inhalation injury - Nguyen, Thai Ngoc Minh; Dao, Thanh Tuyen; Pham, Ngoc Anh; Nguyen, Thi Tu (Tạp chí Y học Thảm hoạ và Bỏng, 2023)
Objective: Evaluate the variation of SpCO index with clinical symptoms, medical support pre-hospital, and mortality rate of inhalation injury patients.Subjects and methods: Prospective descriptive study with longitudinal follow-up in inhalation injury patients at the Intensive Care Unit - Le Huu Trac National Burns Hospital from March 2022 to May 2023. 50 patients with inhalation injuries were hospitalized within the first 72 hours. Patients were treated according to the treatment regimen for inhalation injury and CO poisoning. Subclinical and clinical symptoms were recorded and compared. The data was processed using STATA 16.0 software.Results: The average SpCO index upon admission in the study patients was 15.7%. 24 patients admitted to the hospital before 5 hours had an average SpCO index was 8.3 ± 7.6%. 88% of patients were hospitalized within 12 hours of the accident. Medical support pre-hospital: Oxygen supply 63.3%, endotracheal intubation 35% and mechanical ventilation 25%. Respiratory assessment indicators including SpO2 and average PaO2 were high and had no statistical difference. Patients with a severe grade of inhalation injury have a high SpCO index upon admission. The mortality rate was high (> 70%) and the SpCO index at admission has no relationship with mortality rate.Conclusion: Patients with CO poisoning were hospitalized early, the SpCO index decreased over time and did not correlate with treatment outcome. Patients with more severe inhalation injuries had a higher SpCO index upon admission. Symptoms are non-specific mortality rate was high, causing confusion and making it difficult to diagnose and predict inhalation injury patients.